1962
DOI: 10.1084/jem.116.2.187
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Thymus in Immune Reactions in Rats

Abstract: In the preceding papers (2-4) it has been shown that, in rats thymectomized early in life, there is a partial or complete suppression of immune phenomena of the type attributed to delayed hypersensitivity, specifically of skin sensitization to tuberculin or to purified protein (bovine serum albumin), experimental allergic encephalomyelitis, and skin homograft rejection. Evidence is presented that humoral antibody formation may be diminished as well. The present paper deals with histologic changes found in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

1965
1965
1979
1979

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(37 citation statements)
references
References 20 publications
3
34
0
Order By: Relevance
“…The time agrees much better with the peak of proliferation in germinal centers, as was also noted in previous studies on the spleen (3). This does not suggest a relationship to delayed type sensitivity, since germinal centers are thymus-independent (25,26), and are much more dearly related to the humoral antibody response (27,28) particularly of the 7S anarnnestic type (1, 29,30). The other possible explanation is that the early proliferative response indeed occurs in cells carrying immunological memory for antibody production, but that the majority of these cells are still immature.…”
Section: Discussionmentioning
confidence: 90%
“…The time agrees much better with the peak of proliferation in germinal centers, as was also noted in previous studies on the spleen (3). This does not suggest a relationship to delayed type sensitivity, since germinal centers are thymus-independent (25,26), and are much more dearly related to the humoral antibody response (27,28) particularly of the 7S anarnnestic type (1, 29,30). The other possible explanation is that the early proliferative response indeed occurs in cells carrying immunological memory for antibody production, but that the majority of these cells are still immature.…”
Section: Discussionmentioning
confidence: 90%
“…1, 8, and 10, respectively; center well, normal rat serum. There is complete fusion of the lines formed by ALSo, 1,8, and 10; and partial fusion of the lines formed by ALSB 1 and anti-Ig serum, and by ALSB 8 and anti-Ig serum.…”
Section: Makeup Of Lymphocyte Populations In Txbmmentioning
confidence: 96%
“…Antisera absorbed in this manner have binding properties comparable to those prepared by the more rigorous methods employed in this investigation. DISCUSSION A congeries of evidence from studies in the chicken (19,20), mouse (21-23), rat (1)(2)(3)(4)24), and other mammalian species including man (25) has established the existence of at least two developmentally and functionally distinct populations of lymphocytes. T lymphocytes are produced under the influence of the thymus, whereas B lymphocytes arise from stem cells in the bone marrow and are formed in both normal and thymectomized subjects.…”
Section: Makeup Of Lymphocyte Populations In Txbmmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, and the fact that thymectomy markedly reduced the number of their tumourbearing animals, it was considered that a different immunological mechanism might be involved. The carcinogenicity factor in thymectomized rats might bave been greater had this group of rats lived longer, as immune competence (Waksman et al, 1962) falls off with age in thymectomized rats. Wagner et al (in preparation) found that only carrageenan (an agent cytotoxic for macrophages) among a number of substances, increased the mesothelioma rate.…”
mentioning
confidence: 99%